Rock–water interactions and pollution processes in the volcanic aquifer system of Guadalajara, Mexico, using inverse geochemical modeling. (May 2016) - Morán-Ramírez, J.; Ledesma-Ruiz, R.; Mahlknecht, J.; Ramos-Leal, J.A.
Abstract: In order to understand and mitigate the deterioration of water quality in the aquifer system underlying Guadalajara metropolitan area, an investigation was performed developing geochemical evolution models for assessment of groundwater chemical processes. The models helped not only to conceptualize the groundwater geochemistry, but also to evaluate the relative influence of anthropogenic inputs and natural sources of salinity to the groundwater. Mixing processes, ion exchange, water–rock–water interactions and nitrate pollution and denitrification were identified and confirmed using mass-balance models constraint by information on hydrogeology, groundwater chemistry, lithology and stability of geochemical phases. The water–rock interactions in the volcanic setting produced a dominant NaHCO3 water type, followed by NaMgCaHCO3 and NaCaHCO3 . For geochemical evolution modeling, flow sections were selected representing recharge and non-recharge processes and a variety of mixing conditions. Recharge processes are dominated by dissolution of soil CO2 gas, calcite, gypsum, albite and biotite, and Ca/Na exchange. Non-recharge processes show that the production of carbonic acid and Ca/Na exchange are decreasing, while other minerals such as halite and amorphous SiO2 are precipitated. The origin of nitrate pollution in groundwater are fertilizers in rural plots and wastewater and waste disposal in the urban area. This investigation may help water authorities to adequately address and manage groundwater contamination. Graphical abstract: Highlights: The Inverse geochemical modeling was used to study to processes occurring in a volcanic aquifer. Three flow sections were selected to apply inverse hydrogeochemical modeling. Three main groundwater flows were identified: a local, intermediate and regional flow. The models show that in the study area that groundwater is mixed with local recharge. In the south, the aquifer has thermal influence.